ISSUES OF PROTECTING RIGHTS AND INTERESTS, AS WELL AS THE RESPONSIBILITY OF FANS IN THE FIELD OF PHYSICAL CULTURE AND SPORTS IN THE REPUBLIC OF UZBEKISTAN - Musaev, Elbek T. (International Journal of Psychosocial Rehabilitation, 2020)
In Uzbekistan, during the last three years important changes devoted to the social sphere are performed based on the Section 4 according to Strategy for Action on the five priority areas for the development of Uzbekistan in 2017-2021. Thus, in this article we analyze the legal status of a sports fan, focuses primarily on the rights, obligations, and responsibility of the fan as a subject of sports relations. Based on the analysis of national and foreign legislation, it is proposed to improve the legislation in the field of physical culture and sports in the Republic of Uzbekistan